(K)eine Grenze das Private und das Politische im Nationalsozialismus 1933–1940 - Meyer, Christian 1971- (De Gruyter Oldenbourg, 2020)
For those persecuted by the Nazi regime, an ability to distinguish between the private and political was an essential skill. Exclusion and suppression infused the language of those who emigrated. This study by Christian Meyer expands earlier perspectives on the nature of privacy in National Socialism, which swung between the extreme politicization of private life and a withdrawal to the hidden corners of the "idian
Keywords: Sozialgeschichte 1933-1940; Autobiografie; Historische Semantik; National Socialism in Germany 1933–1940; Nationalsozialismus in Deutschland 1933-1940; autobiography; historical semantics; HISTORY / Europe / Germany; Privatheit; Privatleben; Drittes Reich; Das Politische; Deutschland; Hochschulschrift